'This beautiful appearance … has gradually transformed and become altogether monstrous': the massacre at Troyes as a foreseeable tragedy. (27th December 2022) - Roberts, Penny
Abstract: The massacres that took place in several provincial towns during August, September and October 1572 have attracted far less attention than the intense historical scrutiny given to events in Paris. This relative neglect gives the impression that there is nothing more to say about these episodes of violence except as aftershocks of the main event. Focusing on the case of Troyes in Champagne, this article demonstrates that the provincial massacres are worthy of re-examination. It reconsiders the context of the killing on the streets and in the prison of the town and, in particular, those who were supposedly responsible for ordering the bloodshed. Although it remains impossible to reconstruct a complete picture, the unusual richness of the surviving local sources allows for a more nuanced analysis than provided hitherto and a better-informed understanding of the events as they unfolded.